Meta-analisis Pengembangan LKPD Berbasis Problem Based Learning - Nilam, Nadia; Fitri, Rahmadhani; Selaras, Ganda Hijrah (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
Teaching materials such as LKPD in biology learning are still limited and not yet interactive. The aim of the research was to find out how the validity level of student worksheets in high school biology lessons had been developed by tracing articles that were in accordance with the research. The method used in this research is meta-analysis by taking data from 5 national articles from Google Scholar. The results of the study show that the PBL-based LKPD is valid. Based on the results of observations and discussions conducted, it is known that PBL-based worksheets are valid and appropriate for use in learning.